2014
DOI: 10.1371/journal.pone.0114757
|View full text |Cite
|
Sign up to set email alerts
|

p53-Dependent Activation of microRNA-34a in Response to Etoposide-Induced DNA Damage in Osteosarcoma Cell Lines Not Impaired by Dominant Negative p53 Expression

Abstract: Osteosarcoma (OS) is the most common primary malignant bone tumor and prevalently occurs in the second decade of life. Etoposide, a chemotherapeutic agent used in combined treatments of recurrent human OS, belongs to the topoisomerase inhibitor family and causes DNA breakage. In this study we evaluated the cascade of events determined by etoposide-induced DNA damage in OS cell lines with different p53 status focusing on methylation status and expression of miR-34a that modulate tumor cell growth and cell cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…For example, miR-141 is reported to enhance cisplatin resistance through repression of KEAP1 in ovarian cancer cells, 6 miR-106a induces multi-drug resistance in gastric cancer by targeting RUNX3. 7 In contrast, MiR-200b and miR-15b reverse chemotherapy-induced EMT in human tongue cancer cells by targeting BMI1. 8 The involvement of miRNAs in drug resistance is just beginning to emerge, and more studies are needed to identify other miRNAs, their molecular targets and the processes they affect.…”
Section: Introductionmentioning
confidence: 99%
“…For example, miR-141 is reported to enhance cisplatin resistance through repression of KEAP1 in ovarian cancer cells, 6 miR-106a induces multi-drug resistance in gastric cancer by targeting RUNX3. 7 In contrast, MiR-200b and miR-15b reverse chemotherapy-induced EMT in human tongue cancer cells by targeting BMI1. 8 The involvement of miRNAs in drug resistance is just beginning to emerge, and more studies are needed to identify other miRNAs, their molecular targets and the processes they affect.…”
Section: Introductionmentioning
confidence: 99%
“…Also, in the field of osteosarcoma research, there are much more recent research confirmed that mir-34a can inhibit cell proliferation and promotes apoptosis in human osteosarcoma cells in vitro and in vivo. [21][22][23][24][25][26][27] So, we are valid to consider that mir-34a could inhibit cell proliferation and promotes apoptosis in osteosarcoma possibly. And our results strongly suggest that miR-34a was downregulated in osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, restoration of miR-34a function in OS cells using synthetic miR-34a mimics reduces cell proliferation in intro , and forced expression of miR-34a in OS cells not only inhibits cell proliferation in vitro but also represses tumorigenesis in vivo [26-29]. Nevertheless, there is no report thus far on the utility of systemic administration of a miR-34a agent or combination of miR-34a and chemotherapeutic drug for the treatment of OS in a whole body system.…”
Section: Introductionmentioning
confidence: 99%